How servant leaders navigate conflict: An analysis of Acts 15:36–41 - Craun, Justin R. (HTS teologiese studies, 2022)
Greenleaf’s foundational work on servant leadership has evolved considerably over the past 50 years. Servant leadership has been found to have positive outcomes on group and organisational effectiveness. While servant leadership characteristics and outcomes have been measured, is a need to be better understand how servant leaders navigate when they disagree. Using a social and cultural analysis, the conflict between Paul and Barnabas is explored. Social and cultural analysis allows interpreters to understand what the characters in the narrative ‘see and hear.’ The analysis of Acts 15:36–41 yielded three emerging themes related to how these servant leaders navigated conflict: (1) the tension created by conflict, (2) leader maturity and conflict and (3) the effectiveness of servant leadership amid differences. It was found that servant leaders are not immune from conflict, and when two servant leaders disagree it creates tension between the various servant leader behaviours. Furthermore, a leader’s experience and maturity influence their responses to conflict. Lastly, it was found that servant leaders do not allow conflict to derail their mission.Contribution: This article contributes to the body of knowledge on servant leadership by exploring how servant leaders navigate conflict from a biblical perspective. By exploring servant leadership behaviours from a biblical perspective, this article contributes to the interdisciplinary focus of HTS Teologiese Studies/Theological Studies, engaging social scientific constructs through a New Testament paradigm.